(untitled) (Research, Society and Development, 2021)
The issue of abortion in Brazil is one of the major public health problems today. This situation affronts not only women’s mental and physical health, but also religious, cultural and socio-economic issues in which women are inserted. The study aimed to highlight the emotional factors that result from the abortion process. It is an integrative literature review, where the guiding question was formulated “What are the emotional changes that can affect women after the abortion process?”. A PICo strategy was set up, in which, by means of descriptors and keywords, the following databases were consulted, BIREME (Latin American and Caribbean Center for Health Sciences Information), SCIELO (Scientific Eletronic Library OnLine), MEDLINE (Medical Literature Analysis and Retrieval System Online) served as an instrument for data collection. Only publications that answered the study question, published between 2014 and 2020, in Portuguese, English and Spanish and tests performed on humans were included. 10 studies were selected where they evaluated women from the abortion decision-making process and its reasons, until months later, when the thought of performing the act still lingers. The data presented in this research are intended to present the multifaceted nature of abortion described in the literature whose impact of the loss directly affects the woman’s life. It affects her self-esteem, the way she sees her body, her state of mind and a possible future pregnancy.